2001
DOI: 10.1203/00006450-200106000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Production in Leukocytes during Cerebral Hypoxia and Reoxygenation with 100% or 21% Oxygen in Newborn Piglets

Abstract: The aim of this study was to investigate whether reoxygenation with 21% O 2 rather than 100% O 2 results in reduced hydrogen peroxide (H 2 O 2 ) concentrations in neutrophils (PMN). Piglets (2-4 d old) exposed to severe hypoxia (inspired fraction of oxygen, 0.08) were randomized to resuscitation with 21 (n ϭ 13) or 100% O 2 (n ϭ 12). Five animals served as controls. H 2 O 2 concentrations in PMN in terms of rhodamine 123 (Rho 123) fluorescence intensity from arterial and superior sagittal sinus blood were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…These results are in line with studies showing protective effects of HT (2-4,11-15) and with studies demonstrating harmful effects of hyperoxic reoxygenation (18)(19)(20)(21). The new and important knowledge added by this study is the effect of the combination of these two important interventions recommended by the International Liaison Committee on Resuscitation guidelines (10).…”
Section: Articlessupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in line with studies showing protective effects of HT (2-4,11-15) and with studies demonstrating harmful effects of hyperoxic reoxygenation (18)(19)(20)(21). The new and important knowledge added by this study is the effect of the combination of these two important interventions recommended by the International Liaison Committee on Resuscitation guidelines (10).…”
Section: Articlessupporting
confidence: 90%
“…Evidence from animal studies shows that supplemental oxygen during resuscitation causes significant hyperoxia in the newborn brain (16,17), with increased generation of reactive oxygen species (18), oxidative stress (19), inflammation (20), and cerebral injury (19,21,22). Clinical studies have shown that resuscitation with 100% oxygen has no advantage over air but causes increased mortality (23) and increased time to first breath and/ or cry (24)(25)(26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this and a series of subsequent experiments, we confirmed that 21% oxygen is as efficient as 100% oxygen for resuscitation. [10][11][12][13][14][15][16] The findings in the newborn piglet were consistent, and I realized that the time had come to test our hypothesis in a clinical study. Siddarth Ramji in New Delhi immediately agreed to participate, and the pilot clinical trial was carried out in India, enrolling 84 newborn infants randomized to room air or 100% oxygen resuscitation.…”
Section: Discovery Through a Failurementioning
confidence: 55%
“…An infant suffering severe perinatal asphyxia usually has poor color (cyanosis), perfusion, responsiveness, muscle tone, and respiratory effort, as reflected in a low 5 minute Apgar score. 3 Extreme degrees of asphyxia can cause cardiac arrest and death. If resuscitation is successful, the infant is usually transferred to a neonatal intensive care unit.…”
mentioning
confidence: 99%